FRI0490 The four finger examination technique is superior to the standard two finger technique to detect metacarpal phalangeal joint swelling in rheumatoid arthritis - a validation by power doppler ultrasound. (23rd January 2014) - Keystone, E. C.; Omair, M. A.; Akhaven, P.; Naraghi, A.; Weber, D. A.; Xiong, J.; Mittoo, S.; Weber, M. L.
Abstract : Background: Swollen joints (SJs) are a strong clinical predictor of radiographic progression in rheumatoid arthritis (RA). The metacarpal phalangeal joints (MCP) SJs are particularly relevant since they are the earliest joints demonstrating radiographic progression. Thus, more sensitive detection of less obvious SJs is important for improved assessment of disease activity. A novel four finger (FF) examination technique was developed to be more sensitive than the two finger (TF) technique in the detection of less clinically apparent joint swelling. Objectives: To compare the sensitivity of the FF vs. TF technique to detect synovitis by ultrasound (US). Methods: We compared the FF vs. TF examination technique in 180 MCPs in 18 RA patients. The population was comprised of 94.4% females, mean age of 55.8 yrs and mean disease duration of 19.9 yrs. Patients were examined twice on the same day by 4 rheumatologists; 2 performed FF and 2 used the TF technique. SJs were determined by palpation defined by being either (1) ballotable or (2) spongy (non-ballotable swelling). TJs were also assessed. We evaluated the agreement between the SJ/TJ examination techniques with US using grey scale, power Doppler (PD) positivity, or the presence of an effusion. Results: Consistent with previous literature, the inter-observer agreement (IA) using Kappa statistics was poor to moderate for both SJ techniques. We therefore evaluated only joints in which there was agreement between the 2 examiners for each SJ technique. With the TF and FF techniques respectively, there were 115 & 134 SJs in which there were agreement for the joints being ballotable and 99 & 122 SJs for being spongy. The Kappa agreement between FF and TF techniques respectively, for ballottement by PD was 0.55 vs 0.27; by grey scale 0.35 vs. 0.12, and by effusion: 0.18 vs. 0.08. For SJ detected by being spongy, the relationship between FF and TF was the same, but the Kappas were lower. The agreement between TJs and US was extremely poor with mean Kappas for the 4 examiners for PD of 0.07; for grey scale: 0.06 and for effusion: -0.08. Conclusions: The results of this study demonstrate that for MCPs, the FF technique is more sensitive than the TF technique for detection of synovitis as determined by US and therefore a better examination technique for clinical decision making. Of significance, the data provide strong support for the importance of detecting SJs (rather than TJs) as a prognostic guide for structural damage in RA. Disclosure of Interest: None Declared